MEANS OF DATA ACCESSING ABOUT «TRUE» ADOLESCENT MORBIDITY - V.Yu. Al'bitskiy (Voprosy Sovremennoj Pediatrii, 2011)
With the help of «SOC/PEDIATRIA-3» software we have studied «true» adolescent morbidity from 2006 to 2008 inclusive. We have analyzed data from 723 adolescents including the results of their profound physical examination. We have calculated the index of accumulated morbidity by appealability. We have obtained valid data upon «true» adolescent morbidity. Key words: adolescents, morbidity, database, profound checks. (Voprosy sovremennoi pediatrii — Current Pediatrics. 2011; 10 (3): 12–15)